Hypoxic preacclimatization combining intermittent hypoxia exposure with physical exercise significantly promotes the tolerance to acute hypoxia - Xie, Jiaxin; Xie, Shenwei; Zhong, Zhifeng; Dong, Huaping; Huang, Pei; Zhou, Simin; Tian, Huaijun; Zhang, Jijian; Wu, Yu; Li, Peng (Frontiers in Physiology, 2024)
Background: Both hypoxia exposure and physical exercise before ascending have been proved to promote high altitude acclimatization, whether the combination of these two methods can bring about a better effect remains uncertain. Therefore, we designed this study to evaluate the effect of hypoxic preacclimatization combining intermittent hypoxia exposure (IHE) and physical exercise on the tolerance to acute hypoxia and screen the optimal preacclimatization scheme among the lowlanders.Methods: A total of 120 Han Chinese young men were enrolled and randomly assigned into four groups, including the control group and three experimental groups with hypoxic preacclimatization of 5-day rest, 5-day exercise, and 3-day exercise in a hypobaric chamber, respectively. Main physical parameters for hypoxia acclimatization, AMS incidence, physical and mental capacity were measured for each participant in the hypobaric chamber simulated to the altitude of 4500 m in the effect evaluation stage. The effect was compared between different schemes.Results: During the effect evaluation stage, SpO 2 of the 5-day rest group and 5-day exercise group was significantly higher than that of the control group (p = 0.001 and p = 0.006, respectively). The participants with 5-day rest had significantly lower HR than the controls (p = 0.018). No significant differences of AMS incidence were found among the four groups, while the proportion of AMS headache symptom (moderate and severe vs. mild) was significantly lower in the 3-day exercise group than that in the control group (p = 0.002). The 5-day exercise group had significantly higher V ̇O2 max, than the other three groups (p = 0.033, p < 0.001, and p = 0.023, respectively). The 5-day exercise group also had significantly higher digital symbol and pursuit aiming test scores, while shorter color selection reaction time than the control group (p = 0.005, p = 0.005, and p = 0.004, respectively), Conclusions: Hypoxic preacclimatization combining IHE with physical exercise appears to be efficient in promoting the tolerance to acute hypoxia. Hypoxia duration and physical exercise of moderate intensity are helpful for improvement of SpO 2 and HR, relief of AMS headache symptoms, and enhancement of mental and physical operation capacity.